THE ROLE OF THE SOCIAL MEDIA TIKTOK ACCOUNT @VMULIANA IN IMPROVING PERSONAL BRANDING FOR STUDENTS OF THE STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA - Lathifah Amri Marbun; Anang Anas Azhar (Journal Analytica Islamica, 2025)
This study aims to analyze the role of the TikTok account @vmuliana in enhancing personal branding knowledge among students of the Communication Studies Program at Universitas Islam Negeri Sumatera Utara. Using a descriptive qualitative approach, data were collected through semi-structured interviews with ten senior students and observation of five TikTok videos related to personal branding. The analysis reveals that @vmuliana's content supports students' understanding of key concepts such as value consistency (Unity), digital visibility (Visibility), and personal distinctiveness (Distinctiveness) in building a professional identity. Informative, relatable, and strategically communicated content facilitates the transformation of conceptual knowledge into practical actions, such as optimizing LinkedIn profiles and creating professional resumes. These findings indicate that TikTok can function as an effective informal learning medium for developing students' personal branding skills in the digital age.